2013
DOI: 10.13080/z-a.2013.100.011
|View full text |Cite
|
Sign up to set email alerts
|

Paprastojo kukurūzo (Zea mays L.) drėgmės streso nustatymas, taikant spektrinį atspindį ir klasifikavimo medžio metodą

Abstract: Water stress is one of the most important growth limiting factors in crop production. Several methods have been used to detect and evaluate the effect of water stress on plants. The use of remote sensing is deemed particularly and practically suitable for assessing water stress and implementing appropriate management strategies because it presents unique advantages of repeatability, accuracy, and cost-effectiveness over the ground-based surveys for water stress detection. The objectives of this study were to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 27 publications
4
45
0
4
Order By: Relevance
“…Several previous researches indicated that reduced canopy senescence and higher leaf chlorophyll are correlated with the increasing grain yield in well-watered temperate of hybrids (Lee & Tollenaar, 2007;Barutçular et al, 2016b). The change in leaf morphology induced by deficit water caused higher reflectance in the visible spectra between stressed and unstressed corn leaves (Genc et al, 2013). A significant relationship was observed between SPAD and grain yield in 14 days after anthesis, while no significant association was found during middle and late grain-filling stages (Monneveux et al, 2008).…”
Section: Resultsmentioning
confidence: 91%
“…Several previous researches indicated that reduced canopy senescence and higher leaf chlorophyll are correlated with the increasing grain yield in well-watered temperate of hybrids (Lee & Tollenaar, 2007;Barutçular et al, 2016b). The change in leaf morphology induced by deficit water caused higher reflectance in the visible spectra between stressed and unstressed corn leaves (Genc et al, 2013). A significant relationship was observed between SPAD and grain yield in 14 days after anthesis, while no significant association was found during middle and late grain-filling stages (Monneveux et al, 2008).…”
Section: Resultsmentioning
confidence: 91%
“…However, the decrease in chlorophyll quantification in stressed plants may be a response caused by water deficiency, which degrades the photosynthetic pigments (Genc et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, Genc et al (2013) define that changes in foliar morphology, being these in the concentrations and amount of foliar pigments have a strong influence on the foliar spectral properties. According to Ponzoni et al (2012) chemically it is expected that the decrease of the amount of water causes the degradation of proteins and photosynthetic pigments, which makes the leaf less able to absorb electromagnetic radiation in the visible region and, consequently, reduction of photosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The basis of detecting water stress with remote sensing relates to the difference in reflectance properties of plants under different water stress levels at certain wavelengths in the NIR portion of the electromagnetic spectrum (Genc et al, 2013). The interpretation of these hyperspectral data is complicated by the interrelationships between wavelength variables which require extensive statistical techniques to analyse the data for meaningful information to be derived.…”
Section: A Background On Plant Water Availabilitymentioning
confidence: 99%
“…These indices were developed from the combinations of bands or wavelengths from the NIR (WBI and NDWI) and the SWIR (SIWSI). However, more recently there have been attempts on using the blue, green, red wavelengths or bands (VIS region) and the NIR wavelengths in developing indices to estimate vegetation water content (Genc et al, 2013).…”
Section: B Leaf Water Content and Water Indicesmentioning
confidence: 99%